Toxic Femininity and Competition Among Women in the Workplace: Phenomenological Study of Islamic Ethics, Gender Communication, and Work Psychology - Irianti Usman; Muthiah Umar; Vera Martikasari; Hendar Riyadi (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2025)
This study examines the phenomenon of toxic femininity and unhealthy competition among professional Muslim women in the workplace, focusing on its manifestations, underlying factors, psychological impacts, and coping strategies. Using a phenomenological approach, data were collected through in-depth interviews with four Muslim female informants and analyzed with NVivo software. The findings reveal that toxic femininity manifests in symbolic sabotage, gossip, social exclusion, hierarchical dominance, and the misuse of religious symbols. Contributing factors include professional insecurity, patriarchal culture, and the absence of fair and inclusive organizational policies. The impacts experienced by the informants include chronic stress, psychosomatic symptoms, declining motivation, and social isolation. Coping strategies tend to be personal and spiritual, such as prayer, dhikr, and informal support from family or alumni networks, while collective approaches often fail due to a lack of structural support. This study proposes an integrative 3P model—Psychology, Communication, and Islamic Ethics—as an intervention framework, encompassing the development of psychological safety, ethical communication training, and Islamic leadership grounded in maqashid al-shariah. This model offers a transformative strategy to foster a workplace culture that is just, collaborative, and aligned with Islamic values. Keywords: toxic femininity, queen bee syndrome, organizational psychology, Islamic ethics, gender communication